Reasons of Social Exclusion of Elderly Persons - Čepienė, Aristida; Grigienė, Nina (Social Welfare: Interdisciplinary Approach, 2025)
The article analyses social exclusion experienced by elderly persons living in one-person households in remote rural areas, its reasons and ways of reducing social exclusion. The qualitative research was conducted by employing the structured interview method, whereas the data collected in the study were processed by using deductive thematic analysis. The results of the study have revealed that the elderly encountered financial difficulties, health problems, lack of household utilities, poor infrastructure of their place of residence, challenges of modern technologies, inaccessibility of services and inequality of their provision, limited public transport, challenges in healthcare institutions, a lack of security, and a lack of information. Social exclusion is determined by low self-esteem, psychological experiences, loneliness, a lack of communication, emigration and the loss of loved ones, as well as absence of close neighbours. It is highly important for elderly persons to keep their homes and live in them as long as possible. In order to reduce social exclusion of the elderly, it is of importance to ensure that they can live in their own homes as long as possible, while being provided social services and help at home as needed. It is also relevant to improve the infrastructure of elderships: organisation and financing of transport, advocacy in contacting banks, healthcare facilities and other institutions, adaptation of the environment and residential premises for the elderly; also, it is essential to install security systems and ensure good condition of roads. To reduce social exclusion, it is fundamental to ensure that elderly people should have the opportunity to communicate, which can be achieved through development of volunteer activities and establishment of a mobile psychological service.